Reconstructing spousal rights and obligations in islamic family law through a maqasid-based gender justice approach in the indonesian context - Rina Septiani; Muhammad Saleh; Khurul Anam; La Hanuddin; Yeyen Subandi; Karimuddin Abdullah Lawang (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Contemporary debates on Islamic family law increasingly highlight a critical tension between enduring hierarchical legal formulations and evolving demands for gender justice in pluralistic societies. Despite extensive reform efforts, existing frameworks often fail to translate normative equality into substantive justice, particularly in the distribution of spousal rights and obligations. This study addresses this unresolved gap by reconstructing the conceptual foundation of spousal relations in Indonesian Islamic family law through a maqasid al-shariah–based gender justice approach. Using a qualitative normative–socio-legal design, the research analyzes legal texts, scholarly discourse, and institutional practices to examine how spousal roles are constructed, legitimized, and operationalized. The findings demonstrate that the prevailing legal framework remains structurally anchored in a hierarchical paradigm that equates economic provision with authority, thereby institutionalizing asymmetrical power relations and marginalizing non-material contributions. While material welfare is relatively safeguarded, broader maqasid objectives—particularly justice, reciprocity, and human dignity—are only partially realized. Unlike prior studies that address isolated dimensions of marital inequality, this research advances a comprehensive and integrative framework that reconceptualizes spousal relations as dynamic, reciprocal, and context-sensitive. The study thus moves beyond doctrinal critique by exposing the epistemological limitations of existing interpretations and proposing a relational and substantive justice model grounded in the holistic objectives of Islamic law. This contribution not only enriches Islamic legal scholarship but also positions the study within global discussions on gender, legal reform, and ethical governance. Practically, it provides a conceptual basis for developing more equitable and context-responsive legal interpretations in contemporary Muslim societies.